2017
DOI: 10.1038/s41598-017-09770-5
|View full text |Cite
|
Sign up to set email alerts
|

Decoding finger movement in humans using synergy of EEG cortical current signals

Abstract: The synchronized activity of neuronal populations across multiple distant brain areas may reflect coordinated interactions of large-scale brain networks. Currently, there is no established method to investigate the temporal transitions between these large-scale networks that would allow, for example, to decode finger movements. Here we applied a matrix factorization method employing principal component and temporal independent component analyses to identify brain activity synchronizations. In accordance with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 58 publications
2
22
0
Order By: Relevance
“…The VBMEG method was initially proposed to investigate the dynamic cortical activity of healthy participants during a face recognition task (Fukushima et al, 2015 ). VBMEG has been tested in both simulations (Sato et al, 2004 ; Aihara et al, 2012 ) and healthy volunteer studies (Yoshioka et al, 2008 ; Yoshimura et al, 2012 , 2017 ; Nakamura et al, 2015 ); their main focus was on muscle activity reconstruction and visual stimuli analysis with or without structural and functional MRI constraints. Nevertheless, as a novel brain imaging method, the clinical value of the VBMEG method is yet to be demonstrated regarding its potential to investigate functional brain changes following a brain disease such as a stroke.…”
Section: Introductionmentioning
confidence: 99%
“…The VBMEG method was initially proposed to investigate the dynamic cortical activity of healthy participants during a face recognition task (Fukushima et al, 2015 ). VBMEG has been tested in both simulations (Sato et al, 2004 ; Aihara et al, 2012 ) and healthy volunteer studies (Yoshioka et al, 2008 ; Yoshimura et al, 2012 , 2017 ; Nakamura et al, 2015 ); their main focus was on muscle activity reconstruction and visual stimuli analysis with or without structural and functional MRI constraints. Nevertheless, as a novel brain imaging method, the clinical value of the VBMEG method is yet to be demonstrated regarding its potential to investigate functional brain changes following a brain disease such as a stroke.…”
Section: Introductionmentioning
confidence: 99%
“…The mu-wave is EEG signal with frequency range lies in 8 to 13 Hz. The previous researcher has reported that [6,7,8] the decrease in mu-wave activity over the motor cortex of the brain shows the presence of information processing related to planning, decisionmaking, and preparation of motoric activities.…”
Section: A Emg and Eeg Signal Characteristic On Motoricmentioning
confidence: 98%
“…Biofeedback quantification using electroencephalography (EEG) is also an intensive research [6,7,8] related to motor activities. A mu-wave has reported as one of the parameters for quantifying the level of desynchronization of neuron on the motor cortex [8,9,24].…”
Section: Introductionmentioning
confidence: 99%
“…In the realm of brain-machine interfaces (BMIs), attempts have been made to decode brain activity to allow the input of commands into BMI systems. Due to its practical advantages, electroencephalography (EEG) has been widely used in BMI systems to infer information about intention to move the upper limb [1], targets and distractors [2], finger movement [3], resting states or motor attempts to move the paretic hand [4], intention to stand or sit [5], and intended direction of movement [6,7]. Information that is not directly used could still be useful for improving BMI systems.…”
Section: Introductionmentioning
confidence: 99%